2009
DOI: 10.1016/j.eururo.2008.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Combined Magnetic Resonance Imaging and Magnetic Resonance Spectroscopy Imaging in the Diagnosis of Prostate Cancer: A Systematic Review and Meta-analysis

Abstract: Context: Magnetic resonance imaging (MRI) combined with magnetic resonance spectroscopy imaging (MRSI) emerged as a promising test in the diagnosis of prostate cancer and showed encouraging results.Objective: The aim of this systematic review is to meta-analyse the diagnostic accuracy of combined MRI/MRSI in prostate cancer and to explore risk profiles with highest benefit. Evidence acquisition:The authors searched the MEDLINE and EMBASE databases and the Cochrane Library, and the authors screened reference li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
2
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(65 citation statements)
references
References 43 publications
0
60
2
3
Order By: Relevance
“…Results of T1w/T2w imaging and 1 H-MRS that are consistently suspicious for prostate cancer indicate the presence of cancerous prostate tissue with a probability of approximately 50 % (positive predictive value) with the important differential diagnosis of focal circumscribed prostatitis. Conversely, results of T1w/T2w imaging and 1 H-MRS that are consistently negative indicate the presence of healthy prostate tissue with a probability of approximately 95 % (negative predictive value) with the differential diagnosis of diffuse prostatitis [34]. The sensitivity and specificity of 1 H-MRS combined with individual MRI sequences were 58 % and 93 %, respectively, for the detection of carcinoma of the prostate in a current meta-analysis of 14 studies including a total of 698 patients with a previous negative prostate biopsy [25].…”
Section: Dwi Dce-mri 1 H-mrsmentioning
confidence: 99%
“…Results of T1w/T2w imaging and 1 H-MRS that are consistently suspicious for prostate cancer indicate the presence of cancerous prostate tissue with a probability of approximately 50 % (positive predictive value) with the important differential diagnosis of focal circumscribed prostatitis. Conversely, results of T1w/T2w imaging and 1 H-MRS that are consistently negative indicate the presence of healthy prostate tissue with a probability of approximately 95 % (negative predictive value) with the differential diagnosis of diffuse prostatitis [34]. The sensitivity and specificity of 1 H-MRS combined with individual MRI sequences were 58 % and 93 %, respectively, for the detection of carcinoma of the prostate in a current meta-analysis of 14 studies including a total of 698 patients with a previous negative prostate biopsy [25].…”
Section: Dwi Dce-mri 1 H-mrsmentioning
confidence: 99%
“…This technique allows the integration of anatomical, biological and functional information. Most studies using histopathology specimens as reference standards have shown that mpMRI outperforms conventional anatomical imaging alone for the detection of prostate cancer [33][34][35][36]. There is also evidence that unfavorable findings on mpMRI, especially low ADC values, are associated with adverse histological features [37,38].…”
Section: Mri In Active Surveillancementioning
confidence: 99%
“…Additionally, crosstalk between spectral peaks is problematic. A meta-analysis performed in 2008 found little evidence to recommend clinical adoption of MRSI for diagnosis or targeted biopsy (Umbehr et al, 2009), and more recently a cost-benefit meta-analysis performed in the United Kingdom found expected incremental life years of no more than 0.006 years due to any type of MR-guided biopsy over ultrasound guidance (Mowatt et al, 2013). More recently, good sensitivity (96.4%) but terrible specificity (7.6%) were reported in a MRI-ultrasound fusion guided prostate biopsy study (Salami et al, 2014) fraught with selection and detection bias (Warlick, 2014).…”
Section: Current Pca Imaging Techniquesmentioning
confidence: 99%